DEVELOPMENT OF BLITAR TOURISM PLACE-BASED MATHEMATICS STORY PROBLEM BOOKS - Cindy Rivana; Dwi Kameluh Agustina; Sripit Widiastuti (Universitas Islam Balitar, 2023)
Based on the needs analysis and interviews, it was shown that in learning mathematics, students had difficulty solving word problems related to flat shape material. The purpose of this study was to produce a math word problem book product based on Blitar tourist attractions for learning mathematics with proper flat shape materials. The type of RnD development research that has been developed by Sugiono with six steps, namely (1) looking for potential and problems at SDN Gandekan 2, SDN Kunir 3, and SDN Kunir 2, (2) Conducting research and collection by conducting interviews with class IV teachers, distributing questionnaires student needs and observations of learning mathematics, (3) product design is done by analyzing learning and planning product content, (4) Design validation is carried out by 9 validators consisting of 3 material validators, media validators and language validators, (5) Revision the design was carried out based on expert advice, (6) Conducted readability tests with 5 grade IV students and 5 grade IV teachers. The instrument used in this research is a questionnaire. The feasibility results of the material expert validator are 100%, media experts are 93.5%, and language experts are 91.7%. The results of the teacher's legibility questionnaire obtained a percentage of 95% and the results of the student's readability questionnaire obtained a percentage of 90.4%.